A Systematic Literature Review of Infrastructure Governance: Cross-sectoral Lessons for Transformative Governance Approaches. (February 2023) - Clements, Rebecca; Alizadeh, Tooran; Kamruzzaman, Liton; Searle, Glen; Legacy, Crystal
Infrastructure governance has emerged as a subject of critical interest in the current 'infrastructure turn' whereby fragmented governance approaches sit in tension with complex demands for infrastructure transformations within contexts of multiple intersecting crises. To understand the state of the literature and inform ongoing debates, a systematic review method is used to interrogate a large body of infrastructure governance literature across sectoral boundaries. This review identifies a range of literature gaps prevailing in the areas of infrastructure governance on unceded First Nations land, the societal end goals of infrastructure, and understandings and applications of integrated governance.